Analysis of Vitamin C Levels in Kombucha Tea From Rujak Fruit Skin Waste Using Iodimetric Titration Method - Sri Bulan Nasution; Halimah Fitriani Pane; Melika Ostina Purba; Riri Indriyani; Rabiha Al Husna Rambe (International Journal of Health and Medicine, 2025)
Kombucha tea is a drink produced through a fermentation process of a mixture of tea and sugar using kombucha culture or also called SCOOBY ( Symbiotic Culture of Bacteria and Yeast) . The basic ingredients for making kombucha tea are granulated sugar solution and tea bags, in this study it was varied using fruit skin. Vitamin C is known as an important antioxidant found in many fruits, including in rujak fruit skin which is often considered waste. The purpose of this study was to determine the levels of vitamin C in kombucha tea fermented from fruit skin waste. This study used qualitative and quantitative methods. The qualitative method uses the Benedict test and the quantitative method uses the calculation of the percentage of vitamin C content using the iodimetric titration method. The results of the qualitative analysis of the Benedict test were positive for vitamin C with a change in the color of the sample solution to green-yellowish and the analysis of the percentage of vitamin C content obtained a result of 2.3124% or equal to 0.23124 mg / 10 mL of sample solution. The vitamin C content of kombucha tea can vary depending on the base ingredients used, fermentation time, and storage temperature.